2020
DOI: 10.1007/s11004-020-09885-y
|View full text |Cite
|
Sign up to set email alerts
|

A Coarse-to-Fine Approach for Intelligent Logging Lithology Identification with Extremely Randomized Trees

Abstract: Lithology identification is vital for reservoir exploration and petroleum engineering. Recently, there has been growing interest in using an intelligent logging approach for lithology classification. Machine learning has emerged as a powerful tool in inferring lithology types with the logging curves. However, well logs are susceptible to logging parameter manual entry, borehole conditions and tool calibrations. Most studies in the field of lithology classification with machine learning approaches have focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Neural networks (NN), RF, extreme gradient boosting tree (XGBoost) algorithms, and one-versus-one support vector machines (OVO SVMs) are used to create machine learning (ML) [17]. A coarse-to-fine architecture that incorporates outlier detection, multi-class classification, and a tree-based classifier suggested to identify the lithology using two actuals well logging data sets [19]. A hybrid framework consisting of artificial neural networks and hidden Markov models (ANN-HMM) was suggested for the classification of the lithological sequence [11].…”
Section: Page|78mentioning
confidence: 99%
“…Neural networks (NN), RF, extreme gradient boosting tree (XGBoost) algorithms, and one-versus-one support vector machines (OVO SVMs) are used to create machine learning (ML) [17]. A coarse-to-fine architecture that incorporates outlier detection, multi-class classification, and a tree-based classifier suggested to identify the lithology using two actuals well logging data sets [19]. A hybrid framework consisting of artificial neural networks and hidden Markov models (ANN-HMM) was suggested for the classification of the lithological sequence [11].…”
Section: Page|78mentioning
confidence: 99%
“…Yu et al (2021) compared GBDT, support vector machine, logistic regression, and decision tree models and found that the GBDT algorithm is superior to other algorithms. Xie et al (2021) proposed a coarse-tofine framework that combines outlier detection, multiclass classification with an extremely randomized treebased classifier is proposed to solve these issues. Comparisons are conducted with some baseline machine learning classifiers, namely random forest, gradient tree boosting, and xgboosting.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent optimization algorithms can help solve this problem by automatically searching and optimizing the hyperparameter space to find the best combination of hyperparameters. In the field of lithology identification, some scholars have optimized the parameters of the machine learning model through intelligent optimization algorithm, thus significantly improving the prediction accuracy of lithology identification (Xie et al, 2023). Crow search algorithm is an optimization algorithm based on swarm intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Thermosensitive tactile recognition for mining robot refers to the development of technologies that enable mining robots to perceive and understand their environment using thermosensitive tactile sensors. [ 1 ] This technology has the potential to improve the safety, efficiency, and accuracy of mining operations by enabling robots to navigate and operate in harsh and hazardous environments with minimal human intervention. [ 2 ] Achieving high perceptual sensitivity to heat is heavily influenced by the interactions established between materials in contact.…”
Section: Introductionmentioning
confidence: 99%